Ritual and Religious Practices - Gane, Roy E. (The Oxford handbook of ritual and worship in the Hebrew Bible, 2020)
Ancient near eastern (ANE) rituals and other religious practices fostered relationships with superhuman members of the interactive cosmic community, especially deities, who affected human life. These practices were believed to establish, maintain, restore, or utilize such relationships. The present chapter explores the functions and worldview implications of ANE including biblical Israelite religious practices within the following categories: prayer, sacrificial rituals, non-sacrificial ritual activities including divination and magic, and ritual gestures. Similarities and differences between these and interhuman interactions reflect ANE perspectives regarding the nature of superhumans as personal beings and how to interact with them. The biblical Israelite religious system was more intensely relational than elsewhere in the ANE because the deity YHWH established a covenant with his people and personally resided among them so that they could interact with him more intimately, rather than through idols or other material symbols.